The effect of inoculum and glucose addition on polyhydroxyalkanoate production by Brevibacterium sp. B45 - Diah - RATNANINGRUM; Een Sri ENDAH; Akbar Hanif Dawam ABDULLAH; Vienna SARASWATY; Puspita - LISDIYANTI; Eva - FRASNAWATY; Sri - PRIATINI (Menara Perkebunan, 2021)
Petroleum-based plastics are the major cause of environmental pollution because the plastics need years to be degraded. The difficulties in handling waste of petroleum-based plastic have motivated researchers to produce environmentally friendly plastic materials that are biologically degradable; one of them is polyhydroxyalkanoate (PHA). Polyhydroxyalkanoate is natural biodegradable biopolymers produced by bacteria as an intracellular carbon  and  energy storage. This polymer is an alternative source of plastics  with similar physical properties to petroleum-based plastic.It can be easily biodegraded aerobically and anaerobically. This study examined the potential of one superior isolate as PHA producers, i.e.,Brevibacterium sp. B45. Brevibacterium sp. B45 was cultivated in Ramsay’s minimal medium with inoculum concentrations were 1, 2, and 3% (v/v)and glucose concentrations were 1, 3, and 5% (w/v). The cultivation of  Brevibacterium sp. B45 was carried out in a 500 mL Erlenmeyer flask on a shaker incubator with 150 rpm and 30 oC for 72 hours. PHA recovery was carried out by chloroform extraction and characterized by scanning electron microscopy (SEM), Fourier transformed infrared (FTIR), and differential scanning calorimetric (DSC) methods. The highest yield of dried biomass (2.92%) was obtained using 3% inoculum and 3% glucose. The melting temperature (Tm), enthalpy (ΔHf), and crystallinity (Xc) of the PHA product were 172.1 °C, 61.04 J g-1, and 41.08%, respectively. Data of SEM show that a porous surface characterized morphological of purified PHA grains. The functional units of purified PHA grains were C=O, CH3, C-O, C-O-C, C-C, C-H, and -OH. The purified PHA grains show a similar spectrum to the standard Poly-3-hydroxybutyrate (PHB). Therefore, it could be assumed that PHA produced by Brevibacterium sp. B45 was most likely PHB.